Resveratrol provides neuroprotective effects through modulation of mitochondrial dynamics and ERK1/2 regulated autophagy. (2nd December 2018) - Lin, Kai-Lieh; Lin, Kai-Jung; Wang, Pei-Wen; Chuang, Jiin-Haur; Lin, Hung-Yu; Chen, Shang-Der; Chuang, Yao-Chung; Huang, Sheng-Teng; Tiao, Mao-Meng; Chen, Jin-Bor; Huang, Pei-Hsuan; Liou, Chia-Wei; et al.
Abstract: Mitochondrial dysfunction and oxidative stress are underlying contributors to Parkinson's disease (PD). The reduction of aberrant proteins and dysfunctional mitochondria through constitutive autophagy is essential for neuronal survival. We investigated the neuroprotective effects of the natural red wine extract, resveratrol, on the Complex I inhibitor, rotenone-induced oxidative stress SH-SY5Y cellular model. With rotenone exposure, cellular reactive oxygen species (ROS), apoptosis and cell death increased at both 6 and 18 h; at the same time, mitochondrial membrane potential (ΔΨm) and the balance of mitochondrial dynamic proteins were disrupted, resulting with fragmented mitochondria. Rotenone was also noted to elevate autophagy initiation but downregulate the autophagy flux. Pretreatment with resveratrol to rotenone exposed cells lowered cellular ROS, apoptosis, and increased survival rates. Resveratrol administration also recovered rotenone induced ΔΨm, mitochondria dynamics alteration, and elongated fragmented mitochondria. Both autophagic induction and autophagic flux were enhanced with resveratrol pre-treatment which is compatible with cellular survival. The mitogen-activated protein kinase (MEK) inhibitor, U0126, abolished the rescuing effect of resveratrol on rotenone treated neurons through the inhibition of autophagy flux. Thus, our work implies that the neuroprotective effect of resveratrol works in part through modulation of mitochondria dynamics and upregulating autophagic flux via the MEK/extracellular signal-regulated kinase (ERK) signalling pathway.